Analisis Strategi SOAR Balai Diklat Aparatur Kementerian Kelautan dan Perikanan Menuju Corporate University - Afnan Afnan Fuadi (Widya Cipta - Jurnal Sekretari dan Manajemen, 2020)
Government Training Institutions have very complex challenges and are required to produce quality human resources. In order to increase the capacity and quality of human resources in Ministry of Maritime Affairs and Fisheries, Apparatus Training Center of Ministry of Maritime Affairs and Fisheries has an important role in supporting the achievement of vision and mission and the application of the work culture values of the Ministry of Maritime Affairs and Fisheries. One of the strategic step that can be taken by Apparatus Training Center of the Ministry of Maritime Affairs and Fisheries is to transform into a Corporate University (CorpU). The purpose of this study is to analyze the strategy of Apparatus Training Center of Ministry of Maritime Affairs and Fisheries towards CorpU. This study use SOAR analysis by calculating the IFE-EFE matrix. Based on the result of SOAR analysis, Apparatus Training Center of Ministry of Maritime Affairs and Fisheries is in OA strategy quadrant which is to take advantage of existing opportunities to achieve the expected results by developing a Learning Management System that become a integration center of all knowledge and learning management adaot Apparatus Training Center of Ministry of Maritime Affairs and Fisheries